Determination Of Marketing Area Priority Scale To Enhance Financial Transactions Through Pln Mobile Using Ahp-Topsis Method At Pln Up3 Palembang - Nugroho, Henry; Suparno, Suparno (Jurnal Impresi Indonesia, 2026)
Adoption disparities are influenced by technological infrastructure quality, financial resource availability, and socio-economic readiness (facilitating conditions). To address these challenges, a multi-criteria decision-making approach is required to identify marketing areas with the highest potential for increasing financial transactions through PLN Mobile. This study aims to determine the priority scale of marketing areas that are most effective in improving PLN Mobile’s financial transaction performance by applying the Analytic Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The AHP method is employed to determine the relative importance weights among criteria, while TOPSIS is used to rank alternative areas based on their proximity to the ideal solution. The criteria applied include market potential, technological factors, human resource-related aspects, economic conditions, and quality of services. The results are expected to produce an objective and quantifiable model for determining marketing area priorities. Through this approach, PLN UP3 Palembang can optimize marketing resource allocation and expand digital service adoption among customers across South Sumatra.